Are Nigerian dentists willing to treat patients with HIV infection ? - O. G. Uti; G. A. Agbelusi; S. O. Jeboda (Nigerian Dental Association, 2007)
Objective: HIV/AIDS is a modern day plague, which is a challenge to dentistry. The willingness of dentists to treat HIV positive patients is crucial in the provision of oral health care to this increasing population of patients. The purpose of this study was to assess the willingness of dentists and factors that influence willingness of Nigerian dentists to treat HIV infected patients. Method: A descriptive study of two hundred and fifty dentists practicing in both private and public dental clinics in Southwest Nigeria was carried out. Results: The majority of the dentists (63.6%) expressed willingness to treat HIV infected patients. Willingness of the dentists was significantly associated with gender (p = 0.021), awareness of known HIV patient attending the clinic (p = 0.000), having treated a known HIV patient (p = 0.00), not having fears about HIV (p = 0.001) and attendance at postgraduate courses (p = 0.025). Conclusion: Willingness on the part of the dentists in this study is commendable and it is similar to other African countries. However there is room for more improvement, as any form of unwillingness constitutes a barrier to oral health care for the increasing population of HIV infected patients. There is need for continuing education for dentists to remove the fear of acquiring HIV/AIDS occupationally and improve cross - infection control.